2013
DOI: 10.5324/nje.v23i1.1604
|View full text |Cite
|
Sign up to set email alerts
|

Do Norwegians with diabetes have a healthier diet than the general population?

Abstract: Objective: Review current knowledge about dietary habits among people with diabetes in Norway compared with the general population and nutrient-and food-based dietary recommendations. Method: Baseline dietary data from four intervention studies in subjects with type 2 diabetes, were merged (n=92) and compared with data extracted from a nationwide dietary survey, NORKOST, where participants with diabetes (n=115) were compared with a gender and age matched control group (n=575). A validated food frequency questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…Results from the FFQ assessment at baseline also showed that our participants slightly exceeded the criteria for allowed fibre intake (mean of 32.2 g per day). This indicates that the study population had higher habitual fibre intake than the general population with type 2 diabetes in Norway, and were on the other hand adherent to the Norwegian dietary recommendations of 25–35-g fibre per day [ 58 ]. This may have affected the baseline microbiota composition and diversity and thus its responsiveness to the prebiotic fibre.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the FFQ assessment at baseline also showed that our participants slightly exceeded the criteria for allowed fibre intake (mean of 32.2 g per day). This indicates that the study population had higher habitual fibre intake than the general population with type 2 diabetes in Norway, and were on the other hand adherent to the Norwegian dietary recommendations of 25–35-g fibre per day [ 58 ]. This may have affected the baseline microbiota composition and diversity and thus its responsiveness to the prebiotic fibre.…”
Section: Discussionmentioning
confidence: 99%
“…С другой стороны, важно отметить, в этой группе был более здоровый набор продуктов, как это было отмечено и в нашем исследо-вании, чем в общей популяции, а именно, повышенное потребление овощей, фруктов и ягод, рыбы, ПВ и про-дуктов из цельного зерна, и низким потреблением сла-достей и напитков. В этом отношении, лица с диабетом были ближе к рекомендуемому потреблению, чем общая популяция, хотя их питание, также, не отвечает реко-мендациям в полном объеме [19]. В крупномасштабном обследовании питания больных СД2 населения Японии (1516 участников, средний возраст 59 лет) приведены данные по рациону питания.…”
Section: Discussionunclassified